(untitled) (Latakia University Journal -Medical Sciences Series, 2022)
Background: Neonatal Septicemia (Sepsis) is a life-threatening systemic condition that originates from a bacterial, viral, or fungal infection accompanied with clinical features leading to severe morbidity and mortality. According to recent studies, it is estimated that the incidence of neonatal septicemia based on population is 2,202 per 100,000 births providing that mortality rate ranges between 11% and 19%. Neonatal septicemia is characterized by detecting pathogens in sterile body fluids including bloodstream, given that the most prevalent cause of septicemia are bacteria. which have an increasing rate of resistance to the majority of antibiotics used in-hospitals; especially beta-lactams, the safe, cheap and commonly used antibiotics. Aims: To detect the most frequent bacteria that cause septicemia in neonates and children in Tishreen University Hospital and their prevalence in pediatric department. As well as, to study their antibiotic resistance alteration during the years. Materials and Methods: A total of 642 neonatal and children’s blood samples were tested between December 2018 and December 2021. Blood culture was done by standard microbiological techniques (BACTEC Method) in all the cases; Bacterial isolates were diagnosed using microscopy and traditional culturing, staining and biochemical testing techniques, as well as API determination kits were used in some samples. Chi-square was applied to reveal any significant differences among variants. Results: A total of 139 samples were positive for blood culture (21.7%). CoNS sp. were the most frequent bacterial isolates in our research, followed by Klebsiella sp., Staphylococcus aureus, Acinetobacter sp., pseudomonas aeruginosa, GBS, Streptococcus pneumonia and Proteus sp., respectively. Resistance of CoNS sp. Gram-positive resistance increased significantly during the years 2019-2021 for ampicillin, ceftazidime and meropenem. As for gram-negative resistance, it increased during the years 2019-2021 to amikacin non-significantly.